Model of accumulation of doctor’s experience in expert systems - Супруненко, Оксана Олександрівна; Плотніков, Андрій Володимирович; Філюнова, Олена Германівна (Eastern-European Journal of Enterprise Technologies, 2012)
The problems of representation and processing neverbalizirovannyh knowledge in medical expert systems. The example of the structure of expert system, the features of construction of its subsystems PN-model